2021
DOI: 10.1016/j.burns.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Burn Unit admission and management protocol during COVID-19 pandemic

Abstract: Highlights COVID-19 is an adjunctive risk factor for burn injured patients. Isolation of suspected cases and development of management procedures are essential preventive measures to reduce viral spread. We developed an admission protocol to our Burn Unit which proved itself effective in minimizing the contagion between patients and healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Similar study conducted in Padua University Hospital, Italy, identified only two COVID-19-positive patients out of 35 new burn admissions over the 4-month period. 14 However, epidemiological reports from few other major burn centers during this pandemic, reported no COVID-19-positive burn patient as discussed earlier. 9 10 11 Thus, this study with 16 COVID-19-positive burn cases, which is a good number from a single center, provides good insight for the assessment of TBSA of burns as a risk factor for COVID-19 infection in burns.…”
Section: Discussionmentioning
confidence: 83%
“…Similar study conducted in Padua University Hospital, Italy, identified only two COVID-19-positive patients out of 35 new burn admissions over the 4-month period. 14 However, epidemiological reports from few other major burn centers during this pandemic, reported no COVID-19-positive burn patient as discussed earlier. 9 10 11 Thus, this study with 16 COVID-19-positive burn cases, which is a good number from a single center, provides good insight for the assessment of TBSA of burns as a risk factor for COVID-19 infection in burns.…”
Section: Discussionmentioning
confidence: 83%
“…To avoid a possible spreading of SARS-CoV-2 inside the Burn Unit, and to reduce the risk patients and health workers were submitted to, since the beginning of the emergency period we developed a protocol for the acceptance of all the new patients and the surveillance of the hospitalized ones [17].…”
Section: Discussionmentioning
confidence: 99%
“…In order to face the risk of viral spread, since the beginning of the emergency period, we autonomously developed in our Burn Unit a protocol for the acceptance of all the new patients and the surveillance of the hospitalized ones and the personnel, with distinctions made for the pediatric population [17]. These measures were later followed by the general prevention and management indications established by the Medical Direction of our University Hospital.…”
Section: Burn Unit Experience During the Pandemic Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in the number of admissions in the month of July can be related to the partial lift off of the lockdown in the country allowing movement of patients from different parts of the country to our hospital. It may also be related to the fact that other centers that typically also care for burn patients are busy taking care of COVID 19 cases 17 .…”
Section: Discussionmentioning
confidence: 99%